The Impact of Advertisements on Consumers: A Comparative Analysis of Consumer Laws in Sri Lanka - Shamila, D.L.F. (My University, 2012)
Consumer rights law in this age of globalization has generated new challenges for policy makers to ensure a stable and sustainable community. At the same time, the familiar doctrine ‘let the buyer beware’ is no longer the case with the introduction of consumer rights law. Most manufacturers or marketers introduce a product through television channels, newspapers, world wide websites, notices, exhibitions, and brochures. Advertisements are considered to be the most popular tool for introducing a new product as well as promoting an existing product. Thus, advertisements are expected to bring a positive aspect in the way a consumer would make his decision about the product. At this point, it provides an opportunity to the manufacturers/marketers to divulge prodigiously about the products they produce or market. It should be noted that according to the law of contract, advertisements are considered as mere trade puffing or exaggeration. However, if the advertisements mislead or had induced viewers to purchase a product or engage a service the misrepresentation law will apply. Further, advertising a product should ensure fairness and the free flow of truthful information which depend on credibility and trustworthiness on the part of the advertiser exponent of advertising law. As per Belch and Belch and Ohanian, credibility refers to the extent to which the source is perceived as possessing the expertise required for the communication of the topic and can be trusted to give an objective opinion on the subject. Expertise is derived from knowledge of the subject, and trustworthiness refers to the honesty and believability of the source (McGinnies and Ward 1980). Those dimensions of source expertise and trustworthiness are important to conceptualizing credibility that has been shown to be influential in persuading consumers1. Consumers vary in size and knowledge and it is human psychology that influences decision making. Advertisements can target a group of children, teenagers, women or the public at large. However, it is noteworthy what Franki J’s stated in Annand and Thompson v Trade Practices Commission2 that “the question is to be tested by the effect on a person not particularly intelligent or well informed but perhaps of less than average intelligence and background knowledge […]. The question is not whether the purchaser was deceived but whether the conduct was misleading or deceptive”.